2014
DOI: 10.1016/j.celrep.2014.11.043
|View full text |Cite
|
Sign up to set email alerts
|

The DET1-COP1-HY5 Pathway Constitutes a Multipurpose Signaling Module Regulating Plant Photomorphogenesis and Thermomorphogenesis

Abstract: Developmental plasticity enables plants to respond to elevated ambient temperatures by adapting their shoot architecture. On the cellular level, the basic-helix-loop-helix (bHLH) transcription factor phytochrome interacting factor 4 (PIF4) coordinates this response by activating hormonal modules that in turn regulate growth. In addition to an unknown temperature-sensing mechanism, it is currently not understood how temperature regulates PIF4 activity. Using a forward genetic approach in Arabidopsis thaliana, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
186
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(205 citation statements)
references
References 45 publications
10
186
6
Order By: Relevance
“…Indeed, we found that the expression of SAUR22 was higher at 25°C than at 18°C (Supplemental Fig. S13), which is consistent with previous reports indicating that SAUR19 subfamily members are induced by warm temperatures (Franklin et al, 2011;Delker et al, 2014;Johansson et al, 2014;Bours et al, 2015). This indicates that SAUR19 subfamily genes are regulated by temperature in our growth conditions.…”
Section: Sob3 Binds To the Promoters Of Genes Associated With Auxin Ssupporting
confidence: 81%
“…Indeed, we found that the expression of SAUR22 was higher at 25°C than at 18°C (Supplemental Fig. S13), which is consistent with previous reports indicating that SAUR19 subfamily members are induced by warm temperatures (Franklin et al, 2011;Delker et al, 2014;Johansson et al, 2014;Bours et al, 2015). This indicates that SAUR19 subfamily genes are regulated by temperature in our growth conditions.…”
Section: Sob3 Binds To the Promoters Of Genes Associated With Auxin Ssupporting
confidence: 81%
“…We found QTLs encompassing the EARLY FLOWERING3 (ELF3) gene as a QTL for temperature sensitivity in flowering time in the Col-0/Tsu-0 and Bay/Sha RILs (Thines and Harmon, 2010;Undurraga et al, 2012;Mizuno et al, 2014;Box et al, 2015). Similarly, a QTL around PIF4 was found as a QTL for temperature sensitivity in flowering time in the Col-0/ Tsu-0 population (Brock et al, 2010;Kumar et al, 2012;Delker et al, 2014). The MADS domain transcription factor SVP plays a role in thermal response, it has also been identified as a candidate conferring natural variation through both association mapping and QTL analysis, and its effect is also dependent on the genetic background (Lee et al, , 2013Atwell et al, 2010;Méndez-Vigo et al, 2013).…”
Section: Gwas and Qtl Analysis Identifies Loci Associated With Thermamentioning
confidence: 84%
“…The expression of the transcription factor PHYTOCHROME INTERACTING FACTOR4 (PIF4) is induced at higher temperatures, which in turn leads to the increase in the expression of the YUCCA genes (Franklin et al, 2011). Recently, a role has been demonstrated for DE-ETIOLATED1 (DET1) and ELONGATED HYPOCOTYL5 (HY5) in controlling the hypocotyl elongation response by modulating PIF4 expression according to the ambient temperature (Delker et al, 2014). PIF4 has also been suggested to underlie temperature-induced early flowering in short days (Kumar et al, 2012).…”
mentioning
confidence: 99%
“…The key factor in this warmthmediated arrest on de-etiolation is PIF4. The inactivation of phys by high temperatures stabilizes the protein (Jung et al, 2016;Legris et al, 2016), but also triggers COP1-mediated degradation of HY5, which releases the suppression of PIF4 expression (Delker et al, 2014). High temperature-stabilized PIF4 will continue to keep auxin synthesis high and hypocotyl elongation going, despite the light availability (Franklin et al, 2011).…”
Section: High Temperaturesmentioning
confidence: 99%